Force Transfer through the Scaphotrapeziotrapezoid (STT) Joint - Parody, Nicholas; Huang, Shengnan; Petchprapa, Catherine; Wollstein, Ronit (Journal of Wrist Surgery, 2023)
Background The scaphotrapeziotrapezoidal (STT) joint transfers forces to the proximal carpal row from the thumb and fingers. Clinically, STT joint osteoarthritis is frequently observed on plain radiographs though its role in the mechanics of the wrist joint remains unclear.Questions/Purposes Our purpose was to use a model of normal wrist types, to predict STT motion upon load.Patients and Methods Five normal computed tomography scans of a wrist type 1 and five wrist type 2 were used to model the wrist. A 200-N force was split and applied to the trapezoid and capitate to replicate forces during a knuckle pushup. The bony movement was predicted by the model as bony movement using finite element analysis.Results We found differences in force transfer through the STT joint between the two wrist types when loading the index and middle fingers. Type 1 wrists moved quantitatively more anterior-posterior, type 2 wrists moved more medially-laterally and more proximally-distally. The trapezium in type 1 wrists moved more in the coronal plane than in type 2 wrists. The trapezoid moved more from distal to proximal in a type 2 wrist, p = 0.03.Conclusion/Clinical Relevance This study found differences in motion upon loading through the STT joint between type 1 and 2 wrists. Type 2 wrists moved more radially toward the proximal scaphoid and scapholunate ligament. This study may provide a mechanical basis for degenerative configurations. By linking observed patterns of degeneration to their mechanical causes we can aid in prevention of arthritis.
Keywords: force transfer; lunate type; STT joint; wrist